Clinicomicrobiological study of the removed intrauterine device - Kanakannavar, Suresh S.; S., Ashwini R. (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2019)
Background: Intrauterine contraceptive devices are one of the most efficient, cost effective long acting reversible contraceptives. But the worrying clinical symptoms, misconceptions and higher rates of genital tract infection have become a hurdle in its acceptance as the first choice of contraception. The objective of this study was to study the common reasons for removal of IUCD. Methods: An observational study was done involving 430 women who reported to the OBG Outpatient of the hospitals attached to Bangalore Medical College, over a period of 2 years, for IUCD removal. Socio-demographic details, clinical symptoms compelling IUCD removal were elicited. The removed IUCD was subjected to culture and sensitivity. Initial descriptive analysis was used and statistical tests of significance like chi-square were used to know the relation between genital infections and IUCD. P value <0.05 was considered significant. Results: Of the 430 women, 46.9% were between 21-25 years of age, 49.3% were primipara, and 71% used IUCD for 1-3 years. Most common reason for removal in the first 2 years was heavy menstrual bleed followed by pain abdomen. 15.3% culture reports showed growth of bacteria, with maximum cultures positive in <5 years of usage, the association was statistically significant. Conclusions: Present study shows a lower risk of bacterial infections among IUCD users. Hence, effective counseling regarding the safety of IUCD over other spacing methods is essential to increase its acceptance.